Economic Foundations of Contraceptive Transitions: Theories and a Review of the Evidence - Mahesh Karra; Joshua Wilde (Institute of Labor Economics (IZA), 2023)
We review the foundations of the economic development-contraception nexus, focusing on the pathways through which economic factors drive contraceptive adoption and change. We investigate the channels through which the relationship between economic development and contraceptive dynamics are mediated. Using global data, we document the correlations between economic development and contraception transitions over time and across geographies. We briefly examine the evidence of the role of fertility, both desired and realized, as a central pathway through which the relationship has been historically theorized and empirically verified. We also discuss a range of mechanisms through which economic development drives contraceptive use independently from fertility decline. Finally, we assess the state and quality of evidence of these relationships and propose directions for future inquiry.
Keywords: J13; J16; J11; J18; I12; I15; 330; fertility; contraception; demographic transition; development